Dielectric function of CuBrx I1-x alloy thin films - Seifert, Michael; Krueger, Evgeny; Bar, Michael S.; Merker, Stefan; Von Wenckstern, Holger; Krautscheid, Harald; Grundmann, Marius; Sturm, Chris; Botti, Silvana (Physical Review Materials, 2022)
We study the dielectric function of CuBrxI1-x thin film alloys using spectroscopic ellipsometry in the spectral range between 0.7 eV and 6.4 eV, in combination with first-principles calculations based on density functional theory. Through the comparison of theory and experiment, we attribute features in the dielectric function to electronic transitions at specific k-points in the Brillouin zone. The observed band gap bowing as a function of alloy composition is discussed in terms of different physical and chemical contributions. The band splitting at the top of the valence band due to spin-orbit coupling is found to decrease with increasing Br-concentration, from a value of 660 meV for CuI to 150 meV for CuBr. This result can be understood considering the contribution of copper d orbitals to the valence band maximum as a function of the alloy composition.
CRIS-Team Scopus Importer:2023-04-20